Signals from the niche promote distinct modes of translation initiation to control stem cell differentiation and renewal in the Drosophila testis: research article - Wang, Ruoxu; Roiuk, Mykola; Storer, Freya; Teleman, Aurelio A.; Amoyel, Marc (PLoS biology, 2025)
Stem cells have the unique ability among adult cells to give rise to cells of different identities. To do so, they must change gene expression in response to environmental signals. Much work has focused on how transcription is regulated to achieve these changes; however, in many cell types, transcripts and proteins correlate poorly, indicating that post-transcriptional regulation is important. To assess how translational control can influence stem cell fate, we use the Drosophila testis as a model. The testis niche secretes a ligand to activate the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway in two stem cell populations, germline stem cells (GSCs) and somatic cyst stem cells (CySCs). We find that global translation rates are high in CySCs and decrease during differentiation, and that JAK/STAT signaling regulates translation. To determine how translation was regulated, we knocked down translation initiation factors and found that the cap binding complex, eIF4F, is dispensable in differentiating cells, but is specifically required in CySCs for self-renewal, acting downstream of JAK/STAT activity. Moreover, we identify eIF3d1 as a key regulator of CySC fate, and show that two eIF3d1 residues subject to regulation by phosphorylation are critical to maintain CySC self-renewal. We further show that Casein Kinase II (CkII), which controls eIF3d1 phosphorylation, influences the binding of eIF3d and eIF4F in mammalian cells, and that CkII expression is sufficient to restore CySC function in the absence of JAK/STAT. We propose a model in which niche signals regulate a specific translation programme in which only some mRNAs are translated. The mechanism we identify allows stem cells to switch between modes of translation, adding a layer of regulation on top of transcription and providing cells with the ability to rapidly change gene expression upon receiving external stimuli.